A literatura policial de Patrícia Galvão: um estudo histórico de seus contos como King Shelter - Ribeiro, Francisco Carlos (2022)
The general objective of this research is to examine how fiction literature can be used in an investigation with a historiographical approach. Its specific objective is to analyze how Patrícia Galvão (King Shelter) explored in her detective stories the universe of representations of crime in the context of the crisis of late capitalism. The choice of criminal fiction as a research source for this thesis was due to the social importance of this literary genre, which has exerted an expressive fascination on the reading public since its creation. In turn, Galvão's detective stories were selected as an object of study due to two factors: the relevance of the female presence in Brazilian literature and the scarcity of academic works aimed at examining her criminal fiction production. The research works with the hypothesis that Patrícia Galvão presents in her police narratives the social tensions that characterize the crisis of contemporary bourgeois society. The thesis qualifies as a bibliographical, hermeneutic and qualitative investigation, theoretically based: on the model of analysis of detective fiction literature by Tzvetan Todorov; in Ernest Mandel's Marxist socio-economic critique; and in the anthropophagic cosmovision of the poet Oswald de Andrade. The final product of the research sustains that in her short stories Galvão-Shelter developed a literary dialogue with the three main modalities of police narratives: whodunit, hard-boiled and noir. In this way, using Maurice Leblanc and Georges Simenon as literary references, she managed to carry out a subtle critique of the values of bourgeois-capitalist society. From a chronological perspective, with the publication of her short stories in the magazine Detective, in 1944, Patrícia Galvão became a landmark in Brazilian police literature, having been the first person in the country to publish 12 criminal stories without interruption